2015
DOI: 10.1007/s10534-015-9831-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biological activity of Cu(II), Zn(II) and Re(I) complexes derived from S-benzyldithiocarbazate and 3-acetylcoumarin

Abstract: Cu(II), Zn(II) and Re(I) complexes have been synthesized with the Schiff base, N'-[1-(2-oxo-2H-chromen-3-yl)-ethylidene]-hydrazinecarbodithioic acid benzyl ester (SBCM-H) which was prepared by condensation of S-benzyldithiocarbazate and 3-acetylcoumarin. The metal complexes were characterized on the basis of various physico-chemical and spectroscopic techniques including elemental analysis and electrochemical studies, and FT-IR, UV-Vis, NMR, EPR and mass spectroscopy. The Schiff base was found to behave as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The π-delocalisation of charge and the configurational flexibility of their molecular chain give rise to a great variety of coordination modes [14][15][16][17][18]. Their chemistry and pharmacological applications have been widely investigated as well [1][2][3][4][5][6][15][16][17][18].Coordination compounds, especially those that contain nitrogen-sulphur ligands are synthesized via relatively simple, cost-effective procedures and it has been observed that small changes in their structure, such as change of substituents and their chelation to different metal ions cause great changes in their bioactivities. The coordination of these compounds often lead to enhanced biological activity in several pathogenic fungi [3,[19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The π-delocalisation of charge and the configurational flexibility of their molecular chain give rise to a great variety of coordination modes [14][15][16][17][18]. Their chemistry and pharmacological applications have been widely investigated as well [1][2][3][4][5][6][15][16][17][18].Coordination compounds, especially those that contain nitrogen-sulphur ligands are synthesized via relatively simple, cost-effective procedures and it has been observed that small changes in their structure, such as change of substituents and their chelation to different metal ions cause great changes in their bioactivities. The coordination of these compounds often lead to enhanced biological activity in several pathogenic fungi [3,[19][20][21].…”
mentioning
confidence: 99%
“…The coordination of these compounds often lead to enhanced biological activity in several pathogenic fungi [3,[19][20][21]. Some of these metal complexes have been known to accelerate drug action and the efficacy of a therapeutic agent [1][2][3][4][5][6][19][20][21].The Schiff bases synthesized in this study are the di-2-pyridylketone Schiff bases of isomeric dithiocarbazates, S-2-methylbenzyldithiocarbazate, S-3-methylbenzyl dithiocarbazate and S-4-methylbenzyldithiocarbazate (Fig. 1).…”
mentioning
confidence: 99%
“…4b. The seven-membered ring in CuSBHD has a half-chair conformation with the C4 atom lying 0.9970 (19)…”
Section: Characterization Of the Complexes In The Solid Statementioning
confidence: 99%
“…In many cases, the biological properties of dithiocarbazate derivatives have been shown to be widely different although there may be only slight variation in their molecular structures [8]. Since these ligands possess both hard nitrogen and soft sulfur donor atoms they are capable of coordinating with a wide range of transition and non-transition metal ions forming metal complexes with interesting physicochemical and enhanced biological properties [17][18][19]. The wide diversity of structures displayed by macrocyclic and macroacyclic Schiff bases [20] result in various coordination abilities and lead to potential applications in biology ranging from therapeutics to diagnostics [21].…”
Section: Introductionmentioning
confidence: 99%
“…In biological systems, dithiocarbazates are extensively used as inhibitors of enzymes and for the treatment of cancer. 19,20 In early studies, Bernhardt and co-workers synthesized a series of dithiocarbazate based ligands and their iron(II) complexes and studied their antiproliferative activities. [21][22][23] Recently, Crouse et al reported copper(II) complexes of a series of Sohtun et al: Synthesis, Characterization, Crystal Structure ... dithiocarbazate Schiff base and correlated their structures and their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%